Antioxidant Activity And Tirosinase Inhibition Extract Of Red Shoot Leaves (Syzygium myrtifolium) - Inesha Viata Melika Purba; Edy Fachrial; Roy Indrianto Bangar S (International Journal of Health Engineering and Technology, 2026)
Skin aging is a natural process accelerated by free radical exposure, UV radiation, and environmental pollution, necessitating effective and safe anti-aging agents. This study aimed to evaluate the potential of red shoot leaves ethanol extract (Syzygium myrtifolium) as anti-aging through antioxidant activity and tirosinase enzyme inhibition assays in vitro. Extraction was performed by maceration using 70% ethanol (1:10) for 12 hours, centrifuged, sonicated, and concentrated using a rotary evaporator. Phytochemical skrining identified flavonoids, alkaloids, saponins, tannins, and triterpenoids. DPPH antioxidant assay showed inhibition percentages of 96.17–99.49% at concentrations of 200-800 ppm. Tirosinase inhibition test resulted in 82.54% inhibition. These results demonstrate that red shoot leaves extract has dual anti-aging potential through antioxidant protection and melanogenesis inhibition mechanisms. This study provides scientific basis for developing anti-aging cream formulations based on safe and sustainable local natural ingredients